The Aesthetic Values for Warka Pottery & Jamdet Nasr - Ahmed Jabbar, Nazhah (Opción, 2019)
The civilization of ancient Iraq was characterized by many artistic achieve- ments that reflect the communities affected by the environment, which has become an inspiration in the imagination of the artist through meditation in that nature and the circumstances surrounding it trying to recognize and sense of beauty. The pottery of Warka and Juma Nasr illustrated the culture of that period through the scenes that carry it to form aesthetic values confirming the value and effectiveness of the recipient through formations formed elements of art constitute this aspect of the research problem, as the research targeted the aesthetic contents and the values, concepts and theories affecting the pottery roles through Aesthetic artistic theses have had a clear impact in extrapola- ting the researcher to the artistic work left by those ancient civilizations. According to monitoring and analysis.